2019
DOI: 10.3390/e21090875
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of the Physical Embodiment on the Prefrontal Cortex Activity as Quantified by Its Entropy

Abstract: Computer-mediated-communication (CMC) research suggests that unembodied media can surpass in-person communication due to their utility to bypass the nonverbal components of verbal communication such as physical presence and facial expressions. However, recent results on communicative humanoids suggest the importance of the physical embodiment of conversational partners. These contradictory findings are strengthened by the fact that almost all of these results are based on the subjective assessments of the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 86 publications
(118 reference statements)
0
7
0
1
Order By: Relevance
“…For instance, in the case of mediation, whereas Vyšata et al [ 204 ] reported a decrease in global entropy during the mediation (interpreted as a sign of relaxation by the authors), Kakumanua et al [ 207 ] observed its increase which was only present in the case of experienced meditators. On the other hand, the mediated social communication studies assumed both, lower [ 205 ] and higher [ 208 , 209 ] entropy to indicate such self-assessed feelings as relaxed mood, interest, and the feeling of human presence. Furthermore, the mediated social communication studies were based on a surprisingly limited number of brain sites (e.g., only two forehead sites in [ 205 , 208 , 209 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the case of mediation, whereas Vyšata et al [ 204 ] reported a decrease in global entropy during the mediation (interpreted as a sign of relaxation by the authors), Kakumanua et al [ 207 ] observed its increase which was only present in the case of experienced meditators. On the other hand, the mediated social communication studies assumed both, lower [ 205 ] and higher [ 208 , 209 ] entropy to indicate such self-assessed feelings as relaxed mood, interest, and the feeling of human presence. Furthermore, the mediated social communication studies were based on a surprisingly limited number of brain sites (e.g., only two forehead sites in [ 205 , 208 , 209 ]).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the mediated social communication studies assumed both, lower [ 205 ] and higher [ 208 , 209 ] entropy to indicate such self-assessed feelings as relaxed mood, interest, and the feeling of human presence. Furthermore, the mediated social communication studies were based on a surprisingly limited number of brain sites (e.g., only two forehead sites in [ 205 , 208 , 209 ]). As a result, it was unclear whether the observed changes in entropy were due to the individuals’ interaction with the media or potentially a residue of overall brain signal variability [ 1 , 3 ] which may not necessarily pertain to the effect of stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Kakumanua et al [87] observed an increase in PE that was only present in the case of experienced meditators. This was also the case in mediated social communication in which the lower [86] and higher [88,89] entropy was assumed to highlight such self-assessed feelings as relaxed mood, interest, and the feeling of human presence. Furthermore, the mediated social communication studies were based on a surprisingly limited number of brain sites (e.g., only two forehead sites in [86,88,89]).…”
Section: Discussionmentioning
confidence: 99%
“…This was also the case in mediated social communication in which the lower [ 86 ] and higher [ 88 , 89 ] entropy was assumed to highlight such self-assessed feelings as relaxed mood, interest, and the feeling of human presence. Furthermore, the mediated social communication studies were based on a surprisingly limited number of brain sites (e.g., only two forehead sites in [ 86 , 88 , 89 ]). As a result, it was unclear whether the observed changes in entropy were due to the individuals’ interaction with the media or potentially a residue of overall brain signal variability [ 1 , 3 ] which may not necessarily pertain to the affect of stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Contents of Sections 3.2.2 through 3.2.4 are also appeared in Keshmiri et al . 55 . For the sake of clarity, we provide their outline in this article as well.…”
Section: Methodsmentioning
confidence: 99%